Biomechanical structuring for figure skating - James, H.; Robertson, K.; Powers, N. (1988)
It has been proposed that evaluatton of posture, flexibility, and mobilii of figure skaters would be of assistance to Junior Elite skaters as they develop their skating, and also assist in injury prevention. Skaters who decide to experience the process of b&mechanical structuring for` figure skaters (BSFS) should experience more upright posture, increase freedom of motion, and greater awareness of their bodies In the gravitational field. These changes will influence their performance to greater precision in execution, better balance, and more eflicient muscle use. In addition, they may have greater endurance and a more artistically pleasing program.